Factors and Impact of the Crime of Adultery on Family Unity and Children's Future - Gustiara, Nisa; Susanti, Emilia; Dewi, Erna (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the causal factors and efforts to overcome the crime of adultery so that they can be taken into consideration by someone who is planning to commit the crime of adultery. This research is important because regulations regarding adultery are not yet a solution to prevent adultery, so this research was carried out to find out the criminological causal factors and find out prevention efforts. This research uses normative empirical methods, data collection was carried out through direct interviews with the Bandar Lampung police station to obtain data on crimes of adultery. This is because this research examines legal norms relating to adultery as a social